MITRAL VALVE PATHOLOGY IN CONNECTIVE TISSUE DYSPLASIA - A. V. Bogachev-Prokofiev; A. V. Afanasiev; I. Yu. Zhuravleva; D. P. Demidov; S. I. Zheleznev; O. Yu. Malakhova; Ya. V. Syrtseva; A. M. Karaskov (Российский кардиологический журнал, 2016)
Recently, the main cause of mortality and disability in the world are cardiovascular diseases. By the data from autopsies, valve defects have 4-7% prevalence, and most common are mitral valve defects. Valve prolapse is caused by in-born defect of connective tissue development. Reconstruction surgery continue becoming more common in mitral regurgitation (MR) correction and is more preferable than the valve replacement. Regardless the long history of successful management of MR, official data from most world cardiosurgery centers shows than reconstruction operations are done just in 10-20% cases. Issues on the improvement of the management of patients with connective tissue dysplasia are still open. There is enough literature on laboratory and experimental studies showing benefits and disadvantages of one or other methods, but there are no large clinical trials with sufficient evidence, to confirm or stronly deny differences in clinical outcomes depending on the selection of one or other method.